Does the presence of comorbidities in rheumatoid arthritis patients impact initial tumor necrosis factor inhibitor treatment response and retention rates? - Inel, Tuba Yuce; Kocaer, Sinem Burcu; Dalkılıç, Ediz; Akar, Servet; Koca, Suleyman Serdar; Senel, Abdurrahman Soner; Onen, Fatos (My University, 2025)
Aims: We aimed to evaluate the effect of comorbidities on the first tumor necrosis factor inhibitor (TNFi) treatment response and retention in patients with rheumatoid arthritis (RA). Methods: The study included adult RA patients (with M05 and M06 ICD codes) registered in the TURKBIO database and receiving their first TNFi treatment. Data on demographic, clinical, and laboratory features, disease activity scores, and other follow-up parameters (at the beginning and months 6 and 12) were collected. The Log-Rank test and Kaplan-Meier curve were used to determine the TNFi retention rates. Results: There were 1172 bio-naive RA patients who initiated their first TNFi treatments. The median age (IQR) of the patients was 53 (51-61), and 79.8% (n=935) were women. The most commonly used TNFi was etanercept (38.9%), followed by adalimumab (27.9%), certolizumab (13.8%), golimumab (10.8%), and infliximab (8.7%). The most prevalent comorbidities in patients were hypertension (32.6%), obesity (32.6%), osteoporosis (22.3%), asthma/COPD (17.9%), and diabetes mellitus (15.7%). The presence of comorbidities at the beginning of TNFi treatment did not affect DAS28 CRP responses at months 6 and 12 (p=0.18 and p=0.83, respectively) and the continuation rates of the first TNFi drug. After conducting a thorough analysis that factored in variables including gender, age over 60 years, smoking, serologic status, presence of erosion, and basal disease activity scores, it was determined that there were no statistically significant hazard ratios (HR) for the first TNFi persistence. However, there was a 5% decrease in adherence to the first TNFi drug with an increase in median disease duration (HR 0.95, 95% CI=0.90-1.00, p=0.048). Conclusion: It has been observed that the presence of comorbidities in patients with RA does not significantly affect the TNFi treatment response and retention rate. However, evidence suggests that as the duration of the disease increases, the continuation of the first TNFi drug may decrease.
Keywords: Rheumatoid arthritis; Comorbidity; first TNFi drug survival